2015
DOI: 10.1111/adj.12340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin on crevicular levels of IL‐1β and CCL28 in experimental gingivitis

Abstract: Background: Curcumin has anti-inflammatory properties. The aim of this study was to compare interleukin-1b (IL-1b) and chemokine (C-C motif) ligand 28 (CCL28) levels following a topical application of curcumin (CRM), chlorhexidine (CHX) and chlorhexidine-metronidazole (CHX-MTZ) in an experimental gingivitis human model. Methods: Sixty systemically healthy selected subjects were randomly assigned to one of three topical antigingivitis gels. Each gel was applied twice daily for 10 minutes as the sole method of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
0
27
0
5
Order By: Relevance
“…As an anti‐inflammatory, curcumin mouthwash was found to be almost as good as CHX and hence it may act as an efficacious adjunct to mechanical periodontal therapy (Muglikar et al , ). Similarly, the anti‐inflammatory potential of topical curcumin was found to be comparable with that of CHX‐MTZ and higher than CHX in affecting the levels of IL‐1β and CCL28 (Pulikkotil and Nath, ). Besides curcumin, in another clinical study turmeric mouthwash was found to be useful as an adjunct to mechanical plaque control methods in the prevention of plaque and gingivitis (Waghmare et al , ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 97%
See 1 more Smart Citation
“…As an anti‐inflammatory, curcumin mouthwash was found to be almost as good as CHX and hence it may act as an efficacious adjunct to mechanical periodontal therapy (Muglikar et al , ). Similarly, the anti‐inflammatory potential of topical curcumin was found to be comparable with that of CHX‐MTZ and higher than CHX in affecting the levels of IL‐1β and CCL28 (Pulikkotil and Nath, ). Besides curcumin, in another clinical study turmeric mouthwash was found to be useful as an adjunct to mechanical plaque control methods in the prevention of plaque and gingivitis (Waghmare et al , ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 97%
“…Gingivitis is one of the most common inflammatory periodontal diseases that affect more than 80% of the world's population (Pulikkotil and Nath, ). Curcumin therapy holds high potential as a treatment of gingivitis.…”
Section: Clinical Studies With Curcuminmentioning
confidence: 99%
“…Pulikkotil and Nath[48] are the only ones who evaluated the effect of curcumin oral gel on experimental gingivitis by comparing the levels of IL-1β and chemokine ligand 28 at baseline and 29 days, showing its anti-inflammatory mechanism of action on a molecular level in gingivitis in humans. No studies are reported that assessed the effect of curcumin on postoperative facial or internal swelling after periodontal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It could be commonly utilized as food dye and spice in curries. 1,2,3 In recent years, many researchers discovered that CUR and its derivatives exhibited some amazing properties such as antioxidant, anti-inflammation, anti-microbial, anticancer and anti-mutagenic with low intrinsic toxicity. 4,5 However, its poor water-solubility restricted its practical application in biology to a great degree.…”
Section: Introduction: Curcumin (Cur) (Scheme 1)mentioning
confidence: 99%